Implementation of an Integrated RPS Information System for Monitoring Course Content Alignment and Digital Signature Automation - Eko Afrianto; Ekatri Ayuningsih; Yovi Hairul Bashar (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2026)
This study aimed to design and implement an integrated Semester Learning Plan (RPS) information system to support course content alignment monitoring and digital signature automation in higher education. The research employed a system development–oriented methodology consisting of needs analysis, system design, development, testing, and deployment. The resulting web-based system integrated RPS document management, structured monitoring of instructional alignment, and secure digital signature workflows within a single platform. Functional testing and initial system utilization demonstrated that the system successfully standardized RPS formats, improved the effectiveness of learning implementation monitoring, and significantly reduced approval time through automated digital validation. Role-based access control ensured data security and workflow integrity, while audit logs enhanced traceability and accountability of academic documents. User feedback indicated positive acceptance, improved usability, and better coordination among lecturers, administrators, and quality assurance officers. Overall, the implementation of the integrated RPS information system contributed to increased transparency, efficiency, and accountability in academic planning and governance. The system also supported institutional digital transformation efforts by promoting paperless administration and sustainable academic quality assurance practices.